ASEAN-Russia : Foundations and Future Prospects - Lugg, Amy; Hong, Mark; Sumskiĭ, V. V. (Viktor Vladimirovich) (Book collections on Project MUSE., 2012)
In 2012, Russia assumes the Chairmanship of APEC, and is keen to build on its memberships of both the East Asia Summit (EAS) and the Asia-Europe Meeting (ASEM). Russia is geographically and historically part of Asia and the Asia Pacific, and has been a dialogue partner of ASEAN since 1996. Still, the obstacles of distance and languages have led ASEAN member states and Russia to know and interact little between both sides. As growth poles in the world economy, there is much benefit in greater interaction between their rich economies. To commemorate the 15th Anniversary of the Russia-ASEAN dialogue partnership in 2011, the ASEAN Studies Centre at ISEAS and its counterpart from MGIMO-University, Moscow co-organized a two-day conference that year, in which papers were presented offering perspectives from Russia and the ten ASEAN member states. Representatives from academia, and the public and private sectors offered insights on topics including geopolitics, bilateral relations, business and economics, and culture and education. This is a timely book that affords the reader insights into where ASEAN-Russia relations currently stand and suggests how they can improve and move forward.